Factors affecting purchase intention through the mediating role of consumer trust: A conceptual framework for effective sales management - Leong, Mei Kei *; Loh, E. G. Y. * (School of Hospitality & Service Management, Sunway University, 2021)
Sales management emphasises the reliance on individual salespersons to “push” a firm’s products to attain contractual agreements with a clientele. Personal selling focuses on strengthening customer relationships through trust-building and serving their long-term interest. A trusting selling environment can be nurtured through sales drivers such as salespersons skills or eWOM, and salespersons' big 5 personality traits, which then could lead to increased purchase intention. This study proposes a conceptual framework that can contribute to sales management, particularly for industry practitioners to possibly embrace changes in human resource management and include technology-mediated programmes to enhance sales activity.